2010
DOI: 10.1038/nsmb.1863
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional insights into 5′-ppp RNA pattern recognition by the innate immune receptor RIG-I

Abstract: RIG-I is a cytosolic helicase that senses 5’-ppp-RNA contained in negative strand RNA viruses and triggers innate antiviral immune responses. Calorimetric binding studies establish that the RIG-I C-terminal regulatory domain (CTD) binds to blunt-end double-stranded 5’-ppp-RNA a factor of 17 more tightly than to its single-stranded counterpart. Here we report on the crystal structure of RIG-I CTD domain bound to both blunt-ends of a self-complementary 5’-ppp-dsRNA 12-mer, with interactions involving 5’-pp clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
262
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(280 citation statements)
references
References 36 publications
16
262
1
Order By: Relevance
“…RIG‐I, but not MDA5, primarily recognizes RNA targets with triphosphorylated 5′ end (5′ppp) (Wang et al 2010; Baum et al 2010; Peisley et al 2012), and recent studies reported that RNA with diphosphorylated 5′ end (5′pp) are substrates of RIG‐I as well (Goubau et al , 2014). Therefore, we have performed enrichment of 5′ppp RNA followed by RNA sequencing to query the dsRNA species identified with J2 dsRNA‐seq and to quantify the percentage of the dsRNAs that have 5′ppp.…”
Section: Resultsmentioning
confidence: 99%
“…RIG‐I, but not MDA5, primarily recognizes RNA targets with triphosphorylated 5′ end (5′ppp) (Wang et al 2010; Baum et al 2010; Peisley et al 2012), and recent studies reported that RNA with diphosphorylated 5′ end (5′pp) are substrates of RIG‐I as well (Goubau et al , 2014). Therefore, we have performed enrichment of 5′ppp RNA followed by RNA sequencing to query the dsRNA species identified with J2 dsRNA‐seq and to quantify the percentage of the dsRNAs that have 5′ppp.…”
Section: Resultsmentioning
confidence: 99%
“…1). 28,29 The 5′triphosphate of the RNA establishes strong electrostatic interactions with the conserved positively charged residues of RIG-I. This provides the structural basis for the high affinity and specificity of RIG-I for the duplex RNAs bearing 5′ triphosphates that are generated during viral replication, as opposed to host RNAs generated during normal cellular metabolism ( Fig.…”
Section: Rig-i: Two-component Molecular Machine For Sensing and Respomentioning
confidence: 99%
“…The length and the 5¢-triphosphate (3p) group of RNA are considered to be the most important factors in eliciting antiviral responses, while the sequence seems to be less critical [35][36][37]. We synthesized a panel of short 3p-ssRNA that have 20, 40, 60, and 80 nt with a random sequence of A, U, C, and G, each of which was detected as a single band with expected size by PAGE analysis (Fig.…”
Section: Characterization Of Short Synthetic Ssrna-induced Antiviral mentioning
confidence: 99%